Influence of ice sheet topography on Greenland precipitation during the Eemian interglacial. Issue 18 (24th September 2014) - Merz, N.; Gfeller, G.; Born, A.; Raible, C. C.; Stocker, T. F.; Fischer, H.
Abstract Greenland precipitation and its relationship to the synoptic forcing has been studied for the last interglacial period (i.e., the Eemian) using a set of global climate simulations. We distinguish between precipitation changes due to the Eemian orbital forcing and responses to modifications in the Greenland ice sheet (GrIS) topography. Precipitation changes caused by orbital forcing alone are of moderate amplitude and are largely determined by large‐scale changes in moisture availability. In contrast, changes in GrIS topography lead to distinct precipitation anomalies over Greenland, while the effect on far‐field regions is negligible. The analysis of the simulations reveals the control of the GrIS topography on where moist air masses are orographically lifted and cause substantial precipitation. However, the general moisture availability and the moisture transport associated with typical weather situations remain unchanged in all simulations. A focal point of the study is precipitation at pNEEM, i.e., the suggested deposition site of Eemian ice archived in the North Greenland Eemian ice drilling project (NEEM) ice core. Eemian orbital forcing leads to an increase in summer precipitation at pNEEM, whereas changes in the GrIS topography can result in either increased or decreased precipitation. Transport routes prior to precipitation events at pNEEM show that moisture is predominantly advected from westerly to southerly directions as the GrIS acts as an impassable barrier for easterly moisture transport. One scenario of Eemian melting of northeastern Greenland, however, allows moist air masses from the Norwegian Sea to arrive at pNEEM. Consequently, this GrIS topography would result in transport‐related changes of Eemian wet‐deposited aerosol records.